Sex, lies, and architecture: Brutalism and the search for sexual truth in David Cronenberg's Stereo. Issue 1 (2nd January 2023) - Komar, Sierra
ABSTRACT: This essay explores sexuality as a point of ontological and epistemological impossibility through an analysis of Brutalist architecture, particularly as it appears in David Cronenberg's 1969 film Stereo . Set against the dramatic, concrete backdrop of the University of Toronto Scarborough, the film follows a series of experiments on telepathy that also promise to liberate the true sexuality of those participating. This essay argues, however, that while Stereo's plot depicts an attempt to discover sexual truth, the film's Brutalist setting gestures towards the absence of sexuality as such. Placing the work of Michel Foucault in dialogue with the critical writing that accompanied Brutalism's emergence in the mid-twentieth century, the essay suggests that Brutalism and modern sexuality share a similar understanding of truth as that which is obscured or concealed by discursive forces. It goes on to argue, however, that Brutalism's attempt to access a 'true' architecture failed, resulting in the exposure of an architectural void rather than an architectural essence. Connecting this failure to psychoanalytic theories of sexuality's ontological negativity, the essay concludes that Stereo's link between Brutalism and sexual truth signals the nonexistence of this truth, the failure that greets all attempts to reveal sexuality's true form.